PHYSICAL AND MECHANICAL EVALUATION OF 8-YEARS-OLD ACACIA HYBRID (Acacia mangium x A. auriculiformis) CLONES FOR VARIOUS END USES - S. K. Sharma; S. R. Shukla; M. Sujatha (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2018)
Currently, clonal of forest tree is gaining importance due to the yield improvement and low variability in different wood characteristics. Hybrid trees from clonal forest are importantly characterized in term of wood quality for finding suitable uses. Accordingly, three clones (HD3, K47, H4) of 8-year-old Acacia hybrid (Acacia mangium × A. auriculiformis) were evaluated for inter-clonal comparison of its wood quality by evaluating their physical and mechanical properties as per Indian Standards. All tree clones were studied at breast high including diameter, heartwood content, and physical and mechanic properties. The Dbh of all three clones was around 30–35% and 60–70% greater than pure forms of A. auriculiformis and A. mangium of the same age, respectively. The volumetric shrinkage of all three clones was found to vary from 7.8 to 8.6%. The low shrinkage values may be attributed to higher dimensional stability of the wood of these clones. The data obtained in green and air-dry conditions were used to calculate ‘suitability indices’ with respect to teak (Tectona grandis) which was taken as a reference wood for comparison in India. All the suitability indices that these clones were either comparable or slightly lower than those of pure forms of A. auriculiformis and A. mangium. Less inter-clonal variation was observed in most of the suitability indices. Though, all the three clones were exclusively grown for their use in pulp and paper industry, but the comparative suitability figures for different end uses indicate that these clones could also be used for certain non-structural applications such as tool handles, light packing cases, pallets and light furniture.